If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 76 = 2x + 16 Reorder the terms: 76 = 16 + 2x Solving 76 = 16 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 76 + -2x = 16 + 2x + -2x Combine like terms: 2x + -2x = 0 76 + -2x = 16 + 0 76 + -2x = 16 Add '-76' to each side of the equation. 76 + -76 + -2x = 16 + -76 Combine like terms: 76 + -76 = 0 0 + -2x = 16 + -76 -2x = 16 + -76 Combine like terms: 16 + -76 = -60 -2x = -60 Divide each side by '-2'. x = 30 Simplifying x = 30
| x+2n=15n+23 | | 3a+13=9a | | 13-9x=133-37x | | x+2n=5n+23 | | 3x+(2/5)=4x+(4/5) | | (8x+12)=((5x-5)2) | | 6x-7=79-2x | | 9+4x=18x | | 9y-10=5y-54 | | 6x^4-12x^2= | | (3-4)+4*3*-3= | | 72x^2+56x/9x-7 | | 7(2x-8)-6=14x-62 | | 4(m-2)-7+2m=6(m+5) | | (8x+12)=(5x-5) | | 3z+7=35 | | 6(1/3)= | | 0*X=5 | | 8r+-5=51 | | 16+-9-2(4*3*1/2)= | | 8/3-2i | | -10+2m=8 | | 90+.4x=X | | 16+x^2=49 | | 5/4a+2=22 | | 8/(3-2i) | | 9y+-10=5y+54 | | -4(3y-10)+2(2y+9)= | | 4/3p=16 | | h(t)=5t^2-30t+45 | | 3/2n=15 | | 2(-3)+16-(3+4)= |